The Strategic Role of the Inspectorate as an Internal Supervisor of the Mandailing Natal Regency Government - El Husein, Rusmin; Isnaini, Isnaini; Frensh, Wenggedes (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the strategic role of the Inspectorate as the internal supervisor of the local government of Mandailing Natal Regency in supporting good governance. This study uses a qualitative approach with data collection techniques through in-depth interviews, document studies, and observations. The data was analyzed descriptively to identify the role of the Inspectorate, the legal basis that supports it, and the inhibiting factors faced. The results of the study show that the Inspectorate has a strong legal foundation, including Law Number 23 of 2014, Government Regulation Number 60 of 2008 concerning SPIP, and related regional regulations. The strategic role of the Inspectorate includes supervising the implementation of regional policies, preventing corruption, evaluating OPD performance, and early detection of potential risks. However, the implementation of the supervisory function faces several obstacles, such as limited human resources, lack of budget, suboptimal technology, and intervention from external parties. These findings are in line with the theory of internal oversight which emphasizes the importance of independence, transparency, and accountability in government management. This study recommends strengthening human resource capacity, optimizing information technology, increasing budget allocation, and protecting the independence of the Inspectorate. In conclusion, the Mandailing Natal Regency Inspectorate has an important role in creating a transparent and accountable government. However, to optimize this role, commitment from various parties is needed to overcome existing obstacles.